The Effect of Incorporation of Moringa Oleifera Leaf Extract on Characteristics of Chitosan-Alginate Films for Active Packaging - Riyandari, Baiq Amelia; Rezeki, Yupita Tri; Pratiwi, Yussi; Lestari, Mega Fia (Jurnal Kimia Riset, 2025)
In this research, preparation of chitosan/alginate film incorporated with Moringa oleifera leaf extract (MOE) was successfully developed. These films were characterized using FTIR spectrophotometer to investigate interaction between chitosan-alginate and the extract. Physical characteristics of these films were also identified including thickness, water content, film solubility, and water vapor permeability (WVP). Film characterization showed that chitosan/alginate films with Moringa oleifera extract had been formed. Addition of crude extract of Moringa oleifera did not affect the thickness of films significantly. Addition of Moringa oleifera leaf extract at higher level concentration increased film solubility of films. Meanwhile, water content and water vapor permeability (WVP) decreased with higher concentration of extract. Antioxidant performance, measured using UV-Vis spectrophotometer, revealed that the film with the highest extract concentration achived the greatest radical scavenging activity (RSA), reaching 43.65% after 48 hours. Furthermore, the application of on grapes demonstrated the potential of chitosan-alginate films with Moringa oleifera extract as effective active packaging.